Foraging and substrate-dependent behavioural patterns of Marphysa mossambica (Peters, 1854) in captivity - Lollen, Kenyum; S, Munil Kumar; Chanu, Thongam Ibemcha; Sugumar, Ramkumar; Sahoo, Upasana; Porayil, Layana (Journal of Indian Fisheries Association, 2024)
The present study explores the behavioural and foraging patterns of Marphysa mossambica, a polychaete species of ecological and commercial significance, under controlled laboratory conditions. The primary objective was to assess the influence of habitat structure, specifically the presence or absence of artificial substrate, on the species activity, territorial interactions, and feeding behaviour. Specimens were housed in tanks equipped with plastic tubes (experimental group) or without substrate (control group). Observations revealed that individuals provided with substrate exhibited reduced territorial aggression and more consistent foraging behaviour, typically feeding from within their tubes with minimal exposure. In contrast, individuals in the control group demonstrated heightened territoriality, frequent aggressive encounters, and greater vulnerability. Feeding without substrate also involved more exposure, increasing the risk of stress or predation. These behavioural differences highlight the critical role of substrate in promoting welfare, reducing stress-related behaviours, and supporting stable feeding activity. Nonetheless, the results have practical implications for polychaete aquaculture, emphasizing the need for appropriate habitat structures to optimize rearing conditions and ensure the long-term viability of M. mossambica as a resource in aquaculture